2014
DOI: 10.1126/scitranslmed.3009457
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic molecular imaging of human bladder cancer using a CD47 antibody

Abstract: A combination of optical imaging technologies with cancer-specific molecular imaging agents is a potentially powerful strategy to improve cancer detection and enable image-guided surgery. Bladder cancer is primarily managed endoscopically by white light cystoscopy with suboptimal diagnostic accuracy. Emerging optical imaging technologies hold great potential for improved diagnostic accuracy but lack imaging agents for molecular specificity. Using fluorescently labeled CD47 antibody (anti-CD47) as molecular ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
107
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(110 citation statements)
references
References 36 publications
1
107
0
2
Order By: Relevance
“…are sensitive to blocking anti-CD47 antibodies (233,234,(241)(242)(243)(244)(245)(246)(247)(248)(249)(250). This makes CD47 the first protooncogene that is universally expressed in all cancers; its function is known, and blockade of its function is therapeutic.…”
Section: Cancer Stem Cells and The Therapeutics That Come From Them: mentioning
confidence: 99%
“…are sensitive to blocking anti-CD47 antibodies (233,234,(241)(242)(243)(244)(245)(246)(247)(248)(249)(250). This makes CD47 the first protooncogene that is universally expressed in all cancers; its function is known, and blockade of its function is therapeutic.…”
Section: Cancer Stem Cells and The Therapeutics That Come From Them: mentioning
confidence: 99%
“…In patients lacking CD44v6 in BC tissue, there is a 2.3-fold increased risk of recurrence (95% confidence interval, 1.28-4.08) [41]. Pan et al [42] reported CD47 as a target for blue-light cystoscopy imaging of BC. The study found a sensitivity of 82.9% and a specificity of 90.5% for CD47-targeted imaging of BC.…”
Section: Discussionmentioning
confidence: 99%
“…To achieve this goal, we will need tools to determine which properties of precancerous lesions predict the likelihood of progression to malignant metastatic disease. There are extraordinary opportunities in pushing these boundaries: (i) exploring new imaging technologies, sensors, and agents through engineering advances, (ii) combining blood biomarkers with imaging, and (iii) developing microscopic imaging tools that can be used intraoperatively or during minimally invasive procedures (i.e., microendoscopy) (49). Combining imaging and blood biomarker analysis may be particularly helpful in increasing the accuracy of screening procedures.…”
Section: Imaging Molecular and Cellular Biomarkersmentioning
confidence: 99%
“…Blood tests for circulating tumor DNA, microvesicles, circulating cancer cells, and/or other makers may increase the accuracy of CT screening (42,50,51). Intraoperative imaging with fluorescent affinity ligands or antibodies (52,53) is now a clinical reality, and reports from the first clinical trials are very promising (49,54). These approaches will ultimately change cancer surgery standards by giving surgeons realtime feedback about tumor margins and whether any cancer remains.…”
Section: Imaging Molecular and Cellular Biomarkersmentioning
confidence: 99%